2021
DOI: 10.1021/acs.jpclett.1c03002
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Perovskitoid Engineering at SnO2 Interface toward Highly Efficient and Stable Formamidinium Lead Triiodide Perovskite Solar Cells

Abstract: The black-phase formamidinium lead triiodide (α-FAPbI3) perovskite has turned out to be one of the most efficient light harvesting materials. However, the phase stability of FAPbI3 is a long-standing issue. Herein, we introduce a layer of tetrabutylammonium fluoride (TBAF) on SnO2, which would form an in situ layer of TBAPbI3 perovskitoid at the SnO2/FAPbI3 interface by interacting with PbI2. The results show that this strategy could improve the conductivity of SnO2, passivate the defects in perovskite, improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…CH 3 stretch), and 2954 cm –1 (asym. CH 3 stretch) , of the TOAC molecule shifted to 2856, 2926, and 2957 cm –1 , respectively, for CsFAMA/TOAC, which indicated the existence of strong chemical interactions between TOAC and CsFAMA. ,,, The shifts of the NH 3 + stretching and NH 3 + bending to a lower wavenumber clearly revealed that there are strong hydrogen bonding interactions between TOAC and CsFAMA through the NH 3 + and TOAC (N–H···Cl). ,,, Additionally, the peaks at 1713 cm –1 (CN) for the CsFAMA shifted to 1709 cm –1 upon TOAC passivation, which additionally signifies the strong interaction between TOAC and CsFAMA. , Moreover, the energy-dispersive X-ray (EDX) elemental mapping images of CsFAMA/TOAC film (presented in Figure g) reveal that Cl atoms are distributed uniformly all over the CsFAMA surface. Therefore, both the FT-IR and EDX mapping data demonstrate the successful incorporation of the TOAC into the perovskite layer.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…CH 3 stretch), and 2954 cm –1 (asym. CH 3 stretch) , of the TOAC molecule shifted to 2856, 2926, and 2957 cm –1 , respectively, for CsFAMA/TOAC, which indicated the existence of strong chemical interactions between TOAC and CsFAMA. ,,, The shifts of the NH 3 + stretching and NH 3 + bending to a lower wavenumber clearly revealed that there are strong hydrogen bonding interactions between TOAC and CsFAMA through the NH 3 + and TOAC (N–H···Cl). ,,, Additionally, the peaks at 1713 cm –1 (CN) for the CsFAMA shifted to 1709 cm –1 upon TOAC passivation, which additionally signifies the strong interaction between TOAC and CsFAMA. , Moreover, the energy-dispersive X-ray (EDX) elemental mapping images of CsFAMA/TOAC film (presented in Figure g) reveal that Cl atoms are distributed uniformly all over the CsFAMA surface. Therefore, both the FT-IR and EDX mapping data demonstrate the successful incorporation of the TOAC into the perovskite layer.…”
Section: Resultsmentioning
confidence: 92%
“…CH 3 stretch) , of the TOAC molecule shifted to 2856, 2926, and 2957 cm –1 , respectively, for the treated MAPbI 3 /TOAC, which demonstrated the existence of strong chemical interactions between TOAC and CsFAMA. The shifts of NH 3 + stretching and NH 3 + bending to lower wavenumber show that there are strong interactions between TOAC and MAPbI 3 through hydrogen bonding of NH 3 + and TOAC (N–H···Cl). , The full FT-IR spectra are presented in Figure S4. We investigate the MAPbI 3 /TOAC film surface composition by EDX elemental mapping, where evenly distributed Cl atoms all over the MAPPbI 3 surface are observed (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR spectroscopy of SnO 2 , PVEM, and PVEM–SnO 2 was performed to demonstrate the functional group formation between SnO 2 and PVEM, as shown in Figure a. PVEM–SnO 2 has both characteristic peaks of C–H and Sn–O, which belong to PVEM and SnO 2 . , Furthermore, the O–Sn–O peak belongs to the SnO 2 shift from 650 to 670 cm –1 , indicating that PVEM is incorporated into SnO 2 . We further conducted XPS spectra to confirm the interaction between SnO 2 and PVEM based on Sn atom bonding.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The selection of an efficient ETL requires a material with a good optical transmittance (in the visible range), a high electron mobility, a low production cost, and the energy levels (conduction and valence band energies) that form a good type-2 junction with the energy levels of the chosen perovskite material [ 32 ]. Among all the candidates, SnO 2 stands out as one of the best candidates for ETL due to its wide optical band gap (3.6–4.0 eV), deep conduction band, better transparency, high electron mobility (~240 cm 2 V −1 s −1 ), long carrier diffusion length, excellent chemical stability, and ease of low-temperature preparation (via solution processing) [ 33 , 34 , 35 , 36 ]. Due to its solution processibility, SnO 2 can be printed and bring advantages such as a low production cost, flexibility, easy scalability, and additive manufacturing processes within reach [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%